A one-dimensional implementation of a coupled elasto-plastic model for ductile damage based on the Gurson approach - Naghani, Siamak Fereidooni (2013)
A one-dimensional implementation of a coupled elasto-plastic model based on the Gurson damage model is presented. This numerical implementation applies finite element schemes and simple programming. The theory of damage based on the Gurson model accompanied with computational algorithm simulates deformation of a bar under uniaxial loading considering a variety of isotropic hardening behaviors. Thus, a general form of algorithm in order to simulate damage evolution based on the Gurson approach is offered